The Edinburgh history of education in Scotland - Anderson, R. D. (Robert David); Freeman, Mark, 1974-; Paterson, Lindsay (Edinburgh University Press, 2015)
Leading historians discuss the distinctive and internationally significant history of Scottish education. The distinctiveness and influence of Scotland's educational institutions have played a significant role in the construction of national identity. This book investigates the origins and evolution of the main institutions of Scottish education, bringing together a range of scholars, each an expert on his or her own period, and with interests including - but also ranging beyond - the history of education. From the medieval period to the modern, this book provides a broad picture of Scottish educational history, while also highlighting the particularities and varieties of the Scottish system through the ages: from monastic to secular; from rural to urban; from Latin to Gaelic; from Reformation to Enlightenment and beyond. This is a hugely important reference work for historians and students of education within and beyond Scotland, and essential background reading for teachers and policy-makers. It is also a significant book for anyone interested in the development of modern Scotland, its culture and institutions. Key Features. The first multi-authored history of education in Scotland that covers the whole of its medieval and modern history An unrivalled group of historians and social scientists with extensive expertise in Scottish history Sets new agendas for the future of historical research in Scotland Contributors. David Allan is a Reader in Scottish History at the University of St Andrews. Robert Anderson is Professor Emeritus of Modern History, University of Edinburgh. Christopher R. Bischof is Assistant Professor of History at the University of Richmond. Ewen A. Cameron is Sir William Fraser Professor of Scottish History and Palaeography at the University of Edinburgh. Kimm Curran is an Affiliate Researcher at the University of Glasgow in Theology and Religious Studies. Ian J. Deary is Professor of Differential Psychology at the University of Edinburgh. Elizabeth Ewan is University Research Chair and Professor, Department of History, University of Guelph. John Finlay is Professor of Scots Law at the University of Glasgow. Mark Freeman is a Senior Lecturer at the UCL Institute of Education, University College London. Matthew Hammond is a Research Associate in History in the School of Humanities, University of Glasgow. Stephen Mark Holmes is an Honorary Fellow in the School of Divinity at the University of Edinburgh and Associate Rector of St John's Episcopal Church, Edinburgh. Walter Humes is a Visiting Professor in the School of Education at the University of Stirling. Martin Lawn is an Honorary Research Fellow in the Department of Education at the University of Oxford. Catriona M.M. Macdonald is a Reader in Late-Modern Scottish History at the University of Glasgow. Jane McDermid is a Reader in History at the University of Southampton. Lindy Moore is an independent researcher and former librarian. David Northcroft is a Research Associate of the Elphinstone Institute, University of Aberdeen. Fiona O'Hanlon is a Chancellor's Fellow in the School of Education at the University of Edinburgh. Lindsay Paterson is Professor of Educational Policy, School of Social and Political Science, University of Edinburgh. John Stevenson is a retired Church of Scotland minister who served in the parish ministry before being appointed as General Secretary of the church's Department of Education. Douglas Sutherland is a Tutor in the University of Glasgow's Centre for Open Studies. Stuart Wallace was a Lecturer in History at Newbattle Abbey College (1985-9) and at the Centre for Continuing Education at the University of Edinburgh (1991-2001).